Opinion: Israel's Government Has Declared a War on Women - Gouri, Hamutal (Haaretz, 2023)
As it is poised to pass another bill that will roll back women's rights, Israel's far-right government should not underestimate the power of the rage and courage of women who refuse to see their rights usurped in the name of a conservative, religious and messianic agenda.
Israël
Keywords: 2023-07 July; Benjamin Netanyahou; Democracy; Judicial Coup; Judicial Reform